2020
DOI: 10.1002/pbc.28165
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of parent‐reported sleep problems in pediatric patients with acute lymphoblastic leukemia after induction therapy

Abstract: Objective To assess sleep problems (prevalence and predictors) in pediatric patients with acute lymphoblastic leukemia (ALL) after the most intensive phase of therapy (induction). Methods Patients (≥2 years) treated according to the Dutch ALL‐11 protocol were included. Sleep was measured using parent‐reports and self‐reports (Children's Sleep Habits Questionnaire; CSHQ) and actigraphy. Parental sleep (Medical Outcome Study Sleep Scale) and distress and parenting problems (Distress Thermometer for Parents) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 53 publications
(135 reference statements)
5
29
1
Order By: Relevance
“…Anemia is related to fatigue in adult cancers, 35 but results from pediatric oncology are consistent with our findings that sleep did not differ between those with low blood counts 36 Concordance between patients and caregivers was moderate to low, consistent with the sleep clinic clinical sample, 15 other studies of child sleep in pediatric oncology, 37,38 and studies examining other patient-reported outcome measures of health-related quality of life. 39 The higher rates of sleep problems reported by caregivers relative to patients may be related to patient response shifts that occur as patients adapt to new health circumstances, altering the evaluation of health-related quality of life to view detriments as less significant than caregivers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Anemia is related to fatigue in adult cancers, 35 but results from pediatric oncology are consistent with our findings that sleep did not differ between those with low blood counts 36 Concordance between patients and caregivers was moderate to low, consistent with the sleep clinic clinical sample, 15 other studies of child sleep in pediatric oncology, 37,38 and studies examining other patient-reported outcome measures of health-related quality of life. 39 The higher rates of sleep problems reported by caregivers relative to patients may be related to patient response shifts that occur as patients adapt to new health circumstances, altering the evaluation of health-related quality of life to view detriments as less significant than caregivers.…”
Section: Discussionsupporting
confidence: 83%
“…39 The higher rates of sleep problems reported by caregivers relative to patients may be related to patient response shifts that occur as patients adapt to new health circumstances, altering the evaluation of health-related quality of life to view detriments as less significant than caregivers. 40 Alternatively, Steur and colleagues 37 have suggested previously that patients may report fewer sleep symptoms than caregivers because of repressive coping styles, 41 in which patients minimize symptom experiences as a means of coping. These discrepancies, although expected, highlight the need to use both Daytime impairment (SRI) may be more likely to vary by demographic characteristics such as age and sex than nighttime sleep disturbances (SD).…”
Section: Discussionmentioning
confidence: 99%
“…These children are treated with more chemotherapy compared to lower risk groups, which could explain a higher occurrence of sleep problems as well. Furthermore, the distress associated with being confronted with ALL and subsequent treatment regimen can cause both APRs and sleep problems on its own 66,67 …”
Section: Discussionmentioning
confidence: 99%
“…One hundred fifty‐one families provided written informed consent (response rate 67%) 25 . Parents of 121 pediatric patients with ALL participated at this time point.…”
Section: Resultsmentioning
confidence: 99%
“…Results of this study were derived from the nationwide, longitudinal ALL11 add‐on SLeep in children with Acute lymphoblastic leukemia And their Parents (SLAAP) study ( SLEEP ). A detailed description of the study is described elsewhere 25 . Pediatric patients from 2 years of age and their parents were eligible, if sufficiently fluent in Dutch to complete questionnaires independently, and if the child was being treated according to the DCOG ALL11 protocol in one of the participating pediatric oncology centers in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%